2019
DOI: 10.3390/en12142709
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Prediction Method of Centrifugal Pump Performance Based on a Double Hidden Layer BP Neural Network

Abstract: With the aim of improving the shortcomings of the traditional single hidden layer back propagation (BP) neural network structure and learning algorithm, this paper proposes a centrifugal pump performance prediction method based on the combination of the Levenberg–Marquardt (LM) training algorithm and double hidden layer BP neural network. MATLAB was used to establish a double hidden layer BP neural network prediction model to predict the head and efficiency of a centrifugal pump. The average relative error of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 12 publications
0
33
0
Order By: Relevance
“…e best performing network was chosen based upon the coefficient of correlation (R), mean squared error (MSE), and the computational efficiency in terms of the number of epochs. Many researchers used either R and MSE [64][65][66] or the coefficient of determination (R 2 ) and root mean square error (RMSE) [67][68][69][70] to check the performance of the ANN models. It was found that the BFGS Quasi Newton (BFG) vanquished all other algorithms.…”
Section: Ann Model Developmentmentioning
confidence: 99%
“…e best performing network was chosen based upon the coefficient of correlation (R), mean squared error (MSE), and the computational efficiency in terms of the number of epochs. Many researchers used either R and MSE [64][65][66] or the coefficient of determination (R 2 ) and root mean square error (RMSE) [67][68][69][70] to check the performance of the ANN models. It was found that the BFGS Quasi Newton (BFG) vanquished all other algorithms.…”
Section: Ann Model Developmentmentioning
confidence: 99%
“…Given strong nonlinear mapping capabilities, artificial neural networks can effectively address the variations in the composition of ash and thus be used for a wide range of fuels. Since a neural network does not require any explicit mathematical processing based on theoretical assumptions, it is not limited by the correctness of the relevant theories [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…It is still useful to perform experimental two-phase flow studies. In [11], the Back Propagation (BP) neural network technique is used to predict centrifugal pump performance. It indicates that the BP neural network can realize hydraulic performance prediction to help engineers design centrifugal pumps.…”
Section: Introductionmentioning
confidence: 99%